2022
DOI: 10.3390/ma15093090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strength Properties of Sand Stabilized with Wood Fly Ash (WFA) and Cement

Abstract: The article describes the laboratory evaluation of mixtures of sand modified with wood fly ash (WFA) and additionally stabilized with different amounts of cement. Laboratory research includes determining the California Bearing Ratio (CBR), compressive and indirect tensile strengths of the mixtures, and the resistance of mixtures to freezing/thawing cycles. The aim of the research is to determine if WFA, an alternative material, can improve sand bearing capacity and contribute to strength development while redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The roughness of paper was measured to be 240ml/min for side A upwards and 272ml/min for side A downwards. There was a relation to this scale of roughness Bendtsen as to the pick resistance which was larger for this value of alkaline pH 9.6 and ash content on ignition of 15.4%w/w [12]. The L*,a*,b* values of colour coordinates told us that the paper had a natural blue-red look (Table 3).…”
Section: Acsr000566 3(4)2023mentioning
confidence: 84%
“…The roughness of paper was measured to be 240ml/min for side A upwards and 272ml/min for side A downwards. There was a relation to this scale of roughness Bendtsen as to the pick resistance which was larger for this value of alkaline pH 9.6 and ash content on ignition of 15.4%w/w [12]. The L*,a*,b* values of colour coordinates told us that the paper had a natural blue-red look (Table 3).…”
Section: Acsr000566 3(4)2023mentioning
confidence: 84%
“…Indeed, quartz (SiO 2 ) represents the major constituent (93–95 wt.%), there are several other oxides are incorporated in the natural sand such as iron oxides (FeO, Fe 2 O 3 ), aluminum oxide, lime (CaO), soda (Na 2 O), potash (Kro)… etc. [ 39 , 40 ]. On the other hand, the used TiO 2 R25 composes of a single constituent; rutile phase titanium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Bricks made with the addition of 5-20% marble flour have adequate compressive strength in relation to the values required by standards, and the addition of marble waste does not significantly affect the amount of salt effloresce occurring in the bricks. In turn, Dimter et al [10] determined the mechanical properties (California Bearing Ratio, compressive and intermediate tensile strength and resistance to freeze/thaw cycles) of wood fly ash (WFA) sand mixtures produced with different amounts of cement. It has been shown that WFA has a significant stabilizing effect on the sand mixture and improves its load-bearing capacity.…”
mentioning
confidence: 99%